The role of ZBTB16 in odontogenic differentiation of dental pulp stem cells. (March 2022) - Zhu, Xiaohan; Niu, Chenguang; Chen, Juxiu; Yuan, Keyong; Jin, Qiaoqiao; Hou, Lili; Huang, Zhengwei
Abstract: Objective: Odontogenic differentiation of dental pulp stem cells (DPSCs) is highly controlled by the activation of several transcription factors. The zinc finger and BTB domain-containing 16 ( ZBTB16 ) gene encodes a BTB/POZ domain and zinc finger containing transcription factors and is involved in several biological processes, but little is known about its role in odontogenic differentiation. The main goal of the current study was to determine the role of ZBTB16 in odontogenic differentiation of DPSCs. Design: ZBTB16, runt-related transcription factor 2 ( RUNX2 ), and osterix ( OSX ) were silenced via small-hairpin RNA (shRNA) lentivirus. The odontoblastic differentiation of DPSCs was detected by alkaline phosphatase (ALP) staining, activity measurement, and alizarin red S staining in vitro . The gene and protein expression levels were assessed by RT-qPCR and western blotting. Further, an ectopic implantation experiment was performed to explore the role of ZBTB16 in mineralization regulation in vivo followed by histological examination. Results: The silencing of ZBTB16 attenuated ALP activity and mineralized nodules formation by DPSCs. In addition, knockdown of ZBTB16 impaired the expression of markers involved in odontogenic differentiation, including dentin sialophosphoprotein, dentin matrix acidic phosphoprotein 1, and collagen 1 in vitro and vivo . Silencing the OSX gene suppressed ZBTB16 expression and, in turn, OSX expression decreased after ZBTB16 knockdown. However, shRUNX2 did not suppress ZBTB16 expression and shZBTB16 did not affect RUNX2 expression. Conclusions: ZBTB16 may play an important role in modulating the odontoblastic differentiation of DPSCs and act as a regulator of OSX in a possible feed-back cycle independent of RUNX2 . Highlights: ZBTB16 played a pivotal role in odontogenesis. OSX regulated ZBTB16 expression and ZBTB16 regulated the expression of OSX in turn. The interaction between ZBTB16 and OSX went through a RUNX2-independent pathway.